Shifts in oxidation states of cerium oxide nanoparticles detected inside intact hydrated cells and organelles. (September 2015) - Szymanski, Craig J.; Munusamy, Prabhakaran; Mihai, Cosmin; Xie, Yumei; Hu, Dehong; Gilles, Mary K.; Tyliszczak, Tolek; Thevuthasan, Suntharampillai; Baer, Donald R.; Orr, Galya
Abstract: Cerium oxide nanoparticles (CNPs) have been shown to induce diverse biological effects, ranging from toxic to beneficial. The beneficial effects have been attributed to the potential antioxidant activity of CNPs via certain redox reactions, depending on their oxidation state or Ce 3+ /Ce 4+ ratio. However, this ratio is strongly dependent on the environment and age of the nanoparticles and it is unclear whether and how the complex intracellular environment impacts this ratio and the possible redox reactions of CNPs. To identify any changes in the oxidation state of CNPs in the intracellular environment and better understand their intracellular reactions, we directly quantified the oxidation states of CNPs outside and inside intact hydrated cells and organelles using correlated scanning transmission x-ray and super resolution fluorescence microscopies. By analyzing hundreds of small CNP aggregates, we detected a shift to a higher Ce 3+ /Ce 4+ ratio in CNPs inside versus outside the cells, indicating a net reduction of CNPs in the intracellular environment. We further found a similar ratio in the cytoplasm and in the lysosomes, indicating that the net reduction occurs earlier in the internalization pathway. Together with oxidative stress and toxicity measurements, our observations identify a net reduction of CNPs in the intracellular environment, which is consistent with their involvement in potentially beneficial oxidation reactions, but also point to interactions that can negatively impact the health of the cells.